キョクイキ カイヨウ ニオケル ブツリ カガク セイブツ カイヨウガク ケンキュウ ノ ショウライ テンボウ ニ カンスル ケンキュウ ショウシュウカイ ホウコク - 小達, 恒夫; オダテ, ツネオ; 福地, 光男; フクチ, ミツオ; Odate, Tsuneo; Fukuchi, Mitsuo (2000)
P(論文) 「極域海洋における物理・化学・生物海洋学研究の将来展望」に関する研究小集会を, 国立極地研究所講堂において平成12年2月18日に開催した。参加者は15名であった。近未来に実施予定の南極研究航海計画についての進捗状況が報告された。特に, 南極観測第VI期5カ年計画が始まる2001-2002年シーズンには(JARE-43), 東京大学海洋研究所「白鳳丸」の南極航海が決定している。また, 東京水産大学「海鷹丸」も南極航海を計画している。これら観測船の観測対象海域は国立極地研究所海洋研究グループが立案した「南極海総合研究計画(Antarctic Ocean in Earth System, AOES project)」の観測海域と同一である。「しらせ」も昭和基地の帰路, 同観測海域に到達する。「白鳳丸」と「しらせ」の観測時期の間になる2月にチャーター船を導入できれば, 夏の全期間をカバーしたマルチシップによる時系列観測が行える。こうした海洋観測は, 世界の南極観測史上初の試みである。全観測船で共通に行うコアメジャーメントは, マルチシップ時系列観測の成功に重要であり, 今後のワークショップで引き続き検討する。 A workshop on future science plans for "Physical, chemical and biological oceanography in the Southern Ocean" was held on February 18,2000,at the National Institute of Polar Research with 15 participants. In this workshop ship opportunities in the near future were introduced. In the first year of the Sixth Phase of the Japanese Antarctic Research Expedition (JAREVI program, JARE43-47), which will begin in 2001,two Japanese research vessels, R/V Hakuho Maru (Ocean Research Institute, University of Tokyo) and T/S Umitaka Maru (Tokyo University of Fisheries) will be used in oceanographic studies in the Southern Ocean during December 2001 and January 2002. The target area is around 65°S and 150°E. In addition to these two vessels, Shirase will visit the same area on her return cruise from Syowa Station in mid-March. Moreover, the coordinating committee for the science program "Antarctic Ocean in Earth System (AOES project)" in NIPR is planning to charter a research vessel in February of 2002. When the chartered vessel is employed, multi-ship observations will be conducted in the same sea area. This will be the first time that such time serial observations over the whole summer, using more than one ship, will be done in the Southern Ocean. Core measurements, which are carried out on all vessels, should be important to success of the time series multi-ship observations. We will continue further discussion in coming workshops. departmental bulletin paper